(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
This article analyzes the application of the law passed on 16 April 1850 on appointing bishops in the various dioceses of Mexico, with the aim of examining the limitations of the agreements between the church and the state in the period between 1850 and 1855. The paper argues that the law was a legal framework guaranteeing the negotiation between the federal government, the church hierarchy and the Holy See when it came to appointing bishops. However, the limitations of the law were Rome’s supremacy in the appointing process, the fact that some members of the clergy were looking for a better church career, as well as the role of bishops and the canonry defending what they judged as the rights of the church.